Determination of Cytological and P53 Expression Effects after Waterpipe Using - Faris M. Elmahdi; Lina A. Salim (Current Innovations in Disease and Health Research Vol. 7, 2023)
The goal of this investigation was to look into the cytological alterations and p53 expression in oral mucosa among waterpipe users in the Kingdom of Saudi Arabia (KSA). Waterpipe smoking is a popular activity among young adults worldwide and has been linked to various health problems. Tobacco is one of the most important risk factors for premature death globally. More than 60 toxic chemicals in tobacco can invade the body’s various systems. Oral squamous cell carcinoma (OSCC) is a pathological type of oral cancer, accounting for over 90% of oral cancers. A vast quantity of scientific, clinical and epidemiological data shows that tobacco is associated with the development of oral squamous cell carcinoma, and its carcinogenic pathways may be complicated. A cross-sectional study was conducted during January to October 2022 in KSA. Two oral mucosa samples were collected from 500 volunteers, of which 300 were waterpipe users and 200 were non-users. Samples were stained using the Papanicolaou staining procedure and immunocytochemical method to show the cytological changes and expression of P53. The Papanicolaou staining outcomes revealed four different results: inflammation, infection, atypia and keratinization. Cytological inflammation was identified in 77/300 (25.6%) waterpipe smokers, which was higher than in non-users (12/200, 6%). Conversely, cytological infection and atypia were observed more commonly in waterpipe smokers than in controls (9% vs. 4.5% and 4.3% vs. 0.5%, respectively), while keratinization was only detected in waterpipe users (3.6%) compared to non-users. Additionally, waterpipe users exhibited higher p53 protein expression compared to non-users. These findings imply that usage of a waterpipe causes specific alterations in the oral mucosa, including elevated p53 expression in abnormal and keratinizing cells. The possible prognosis of oral mucosal lesions that may be malignant, however, may not be determined solely by the presence or lack of p53 staining.